Evaluasi Persepsi Dan Kegunaan Pengguna Terhadap Sistem Pembayaran Qr Code Lintas Batas Di Indonesia: Evaluation of User Perceptions and Utility Regarding Cross-Border QR Code Payment Systems in Indonesia - Nurillah Jamil Achmawati Novel; Nenden Kostini; Sharon Ong Yong Yee (MANAGER: Journal of Management and Administration Science, 2026)
The rapid expansion of digital payment technologies in Southeast Asia has sparked significant interest in cross-border QR code payment systems as instruments for financial integration. While the Quick Response Code Indonesian Standard (QRIS) has evolved into a mandatory national digital payment infrastructure in Indonesia, empirical evidence regarding user perceptions, utility, and the determinants of acceptance for cross-border QRIS remains limited. This study evaluates perceptions and the utility of QRIS as a cross-border payment system in Indonesia and identifies factors influencing its adoption, focusing on the impact of Perceived Ease of Use (PEOU) and Perceived Usefulness (PU) on user acceptance within the Technology Acceptance Model (TAM) framework. This quantitative pilot study employed a structured online survey of 60 experienced adult QRIS users—selected via purposive sampling—and utilized multiple linear regression to examine the simultaneous effects of PEOU (X1) and PU (X2) on user acceptance (Y). The results indicate that the model explains 41.49% of the variance in user acceptance (R²=0.415; Adjusted R²=0.394) and is statistically significant (F=20.208; p<0.05). Perceived Usefulness (X2) significantly influenced user acceptance (β=0.579; p=0.004), whereas Perceived Ease of Use (X1) did not (β=0.087; p=0.225). Descriptive findings reveal that users hold positive perceptions of QRIS regarding utility, ease of use, security, and reliability. Perceived Usefulness was identified as the primary driver of cross-border QRIS adoption, suggesting that functional value becomes a decisive factor once system familiarity is established. Policymakers are advised to strengthen the functional value of cross-border QRIS through enhanced interoperability, reliability, and security communication. This study contributes initial empirical evidence regarding cross-border QRIS adoption for policymakers and digital payment providers in ASEAN emerging markets.